Services trade and investment liberalisation, and domestic regulation : a summary of six country case studies - Chanda, Rupa (CUTS Centre for International trade, Economics & Environment JaipurIN, 2008)
Attempts to pull together cross country experiences on domestic regulation of services and services trade and investment, liberalisation, and to analyze the associated outcomes and regulatory concerns. Examines six developing countries, including Jamaica, in terms of the evolution of their service sectors, their liberalisation experience and results, their regulation concerns and challenges, and their multilateral and regional strategies for undertaking commitments in the service sector.